BIOM-39. P-ERK ASSOCIATION WITH OVERALL SURVIVAL IN RECURRENT GBM PATIENTS TREATED WITH INTRACEREBRAL ADMINISTRATION OF PD-1 AND CTLA-4 BLOCKING ANTIBODIES. (14th November 2022) - Arrieta, Victor; Duerinck, Johnny; Burdett, Kirsten B; Geens, Wietse; Schwarze, Julia Katharina; Gould, Andrew; Chen, Li; McCord, Matthew; Horbinski, Craig; Zhang, Hui; Stupp, Roger; Neyns, Bart; et al.
Abstract: INTRODUCTION: Anti-PD-1 immunotherapy induces clinical responses in a subset of glioblastoma (GBM) patients. We previously reported that ERK1/2 phosphorylation (p-ERK) in pre-treatment tumor samples is predictive of overall survival (OS) following adjuvant anti-PD-1 therapy in two independent cohorts of recurrent GBM patients. METHODS: Following the Remark criteria for biomarker validation, we investigated p-ERK as a predictive of OS in 24 evaluable tumor samples of recurrent GBM patients from a clinical trial. These patients underwent intracerebral administration of immune checkpoint inhibitors as part of a phase I clinical trial where intracerebral administration of ipilimumab (10 mg) or ipilimumab (5 mg) and nivolumab (10 mg) followed by postsurgical intravenous nivolumab (10 mg) was evaluated (NCT03233152; Duerinck J, et al. JITC, 2021). We quantified cell density of p-ERK + cells in tumor regions. For exploratory purposes, patients were divided in 3 groups (n=8 per group) bases on p-ERK cell density. RESULTS: We observed an incremental OS with high p-ERK GBM patients exhibiting a median OS of 81.6 weeks (95% CI 33.86-NA), intermediate p-ERK median OS of 43.1 weeks (95% CI 33.14-NA), and low p-ERK group with a median OS of 19.3 weeks (95% CI 16.14-NA). A Cox proportional hazards model adjusted for age and IDH mutant status showed a trend for p-ERK association with favorable OS (HR= 0.77, 95% CI 0.6-=1.01, P=0.056). CONCLUSIONS: While the number of patients analyzed is relatively small, this study suggests the potential predictive power of p-ERK in an independent prospective GBM cohort treated with an alternative and unique administration approach of immune checkpoint blockade.